The Effect of Work-Life Balance, Burnout, and Work Discipline on Employee Productivity at JTV Rek Surabaya - Marselia Bilqis Rafifah; Acep Samsudin (Lavish Opulent Education, 2025)
This research aims to analyze the effect of work-life balance, burnout, and work discipline on employee productivity at JTV Rek Surabaya. The research employs a quantitative approach using multiple linear regression analysis. The sample consists of employees at JTV Rek Surabaya selected through purposive sampling. The results show that work-life balance has a significant positive effect on employee productivity. Burnout has a significant negative impact on employee productivity, while work discipline contributes positively to improving productivity. Simultaneously, these three variables significantly influence employee productivity. This research is expected to provide practical benefits for the company's management in maintaining work-life balance, reducing the risk of burnout, and enhancing employee discipline to achieve optimal productivity and to develop more effective human resource management strategies.